A study of quality of life among perimenopausal women in selected coastal areas of Karnataka, India - Gayathry Nayak; Asha Kamath; Pratap Kumar; Anjali Rao (Wolters Kluwer Medknow Publications, 2012)
Background: To study the menopause related symptoms affecting the quality of life (QOL) of perimenopausal women in order to understand the prevalence and plan for the interventions. Materials and Methods: Two hundred and nine women were evaluated for perimenopausal symptoms using a 29 item MENQOL questionnaire. Results: The physical and psychosocial symptoms were found to be more prevalent than the vasomotor and sexual symptoms. Conclusion: Perimenopausal symptoms widely vary in women populations, accurate recording and understanding of which is essential to plan effective interventions to improve the QOL.